2016
DOI: 10.1073/pnas.1606113113
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasmodium vivax Duffy-binding protein 1 in invasion of Duffy-null Africans

Abstract: The ability of the malaria parasite Plasmodium vivax to invade erythrocytes is dependent on the expression of the Duffy blood group antigen on erythrocytes. Consequently, Africans who are null for the Duffy antigen are not susceptible to P. vivax infections. Recently, P. vivax infections in Duffy-null Africans have been documented, raising the possibility that P. vivax, a virulent pathogen in other parts of the world, may expand malarial disease in Africa. P. vivax binds the Duffy blood group antigen through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(142 citation statements)
references
References 56 publications
6
130
0
6
Order By: Relevance
“…Similarly, a recent study also showed evidence of EBP2 binding to both Duffy-positive and Duffy-negative erythrocytes, though at low frequency (23). During receptor binding, the DBP ligand domain has been shown to form a homodimer with the N-terminal extracellular domain of DARC (24).…”
Section: Observationmentioning
confidence: 60%
“…Similarly, a recent study also showed evidence of EBP2 binding to both Duffy-positive and Duffy-negative erythrocytes, though at low frequency (23). During receptor binding, the DBP ligand domain has been shown to form a homodimer with the N-terminal extracellular domain of DARC (24).…”
Section: Observationmentioning
confidence: 60%
“…Since then, this hypothesis has been challenged by Hostetler et al [18] who found that PvDBP gene duplications were widespread even in malaria endemic areas in Southeast Asia where Duffy-negativity is not present. Another recent study [19] reported evidence of PvDBP gene amplification (3 and 8 copies) in two Duffynegative Ethiopian isolates. In addition, sequence data generated from a P. vivax field isolate (C127 isolate from Cambodia), which used reconstruction of long reads without relying on the reference genome (e.g.…”
Section: Author Summarymentioning
confidence: 93%
“…Gunalan et al . [64] recently analyzed P. vivax isolates from two DARC-negative Ethiopians and described a novel copy number expansion of the Pv DBP gene. The authors proposed that this expansion may facilitate binding to a low-affinity receptor, though experimental support through the identification of this receptor is currently lacking.…”
Section: Plasmodium Vivax: a Long Neglected Pandemicmentioning
confidence: 99%